2011
DOI: 10.1159/000330053
|View full text |Cite
|
Sign up to set email alerts
|

Histological Presence of <i>Helicobacter pylori</i> Bacteria in the Trabeculum and Iris of Patients with Primary Open-Angle Glaucoma

Abstract: Purpose: To investigate the role of Helicobacter pylori in primary open-angle glaucoma (POAG) pathophysiology by detecting its presence in eye biopsies of POAG patients during trabeculectomy. Patients and Methods: Fifty-one consecutive patients who underwent trabeculectomy for POAG not responsive to antiglaucoma therapy, and 35 consecutive anemic controls were examined for H. pylori presence mainly by gastric mucosa histology. In POAG patients, eye biopsies were also obtained and stained for H. pylori presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 67 publications
(49 reference statements)
1
36
0
4
Order By: Relevance
“…In our new study published this year,2 we show for the first time the existence of H. pylori bacteria in the trabeculum and iris specimens of glaucoma patients, thereby further supporting the role for H. pylori infection in the pathophysiology of primary open-angle glaucoma. Specifically, the study included 51 consecutive patients who underwent trabeculectomy for primary open-angle glaucoma not responsive to topical antiglaucoma therapy.…”
supporting
confidence: 62%
“…In our new study published this year,2 we show for the first time the existence of H. pylori bacteria in the trabeculum and iris specimens of glaucoma patients, thereby further supporting the role for H. pylori infection in the pathophysiology of primary open-angle glaucoma. Specifically, the study included 51 consecutive patients who underwent trabeculectomy for primary open-angle glaucoma not responsive to topical antiglaucoma therapy.…”
supporting
confidence: 62%
“…The authors suggested a variety of underlying mechanisms, including the induction of inflammatory responses, as well as apoptotic processes that could lead to glaucomatic neuropathy. The study of Zavos et al [48] detected H. pylori organisms using cresyl fast violet stain on histology preparations of tissue samples of trabeculum and iris, taken from the patients who underwent surgical trabeculotomy for open-angle glaucoma, and who tested positive for gastric H. pylori infection. In addition, Zavos et al [49] evaluated gastric biopsy specimens from 43 patients with open-angle glaucoma for the presence of H. pylori and expression of genes, involved in cell proliferation and apoptosis (Ki-67, p53, Bcl-2) as well as indices of cellular immune surveillance (T-and B-lymphocytes).…”
Section: Ophthalmology Skin and Oral Mucosa Diseasesmentioning
confidence: 99%
“…Likewise, Hp may access the brain via the oral−nasal−olfactory pathway, leading to neurodegeneration . An original study revealed Hp contamination and neutrophilic and lymphocytic infiltration in the HTM and iris tissue of glaucomatous patients after surgical intervention. This suggests an Hp ‐I−induced chronic inflammatory process leading to glaucomatous damage.…”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 99%